Antibodies to Heterologous Proteins in Hemophilia A Patients Receiving Recombinant Factor VIII (Recombinate™) - Ingerslev, Jørgen; Christiansen, Kirsten; Ravn, Hanne B.; Bray, Gordon L.; Gomperts, Edward D.; The Recombinate Study Group (Thrombosis and Haemostasis, 2002)
As a consequence of the manufacturing process, trace quantities of Chinese hamster ovary cell protein, bovine serum albumin and murine immunoglobulin G are present in Recombinate™ recombinant human factor VIII (rhFVIII). The development of antibodies (Abs) to these heterologous proteins was evaluated during long-term rhFVIII therapy of hemophilia A in 68 previously treated and 73 previously untreated patients. Ab prevalence was also assessed in 157 non-hemophilic subjects. Abs against heterologous proteins could be detected in varying percentages of patients and non-hemophilic subjects. Abs arose in patients sporadically, and levels were typically low. There were no adverse events associated with development or presence of anti-heterologous protein Abs. These data indicate that sustained immune responses to trace levels of heterologous proteins are very infrequent during long-term rhFVIII therapy.
Keywords: Factor VIII; recombinant proteins; CHO cells; antibodies; monoclonal; serum albumin; bovine